Assessment of the Level of Development of Cashless Transactions in the European Union Countries Between 2019–2023 - Apanel, Adrian; Grzelczak, Marlena (Journal of Finance and Financial Law, 2025)
The purpose of the article. The aim of the article is to assess the level of development of cashless payment in the European Union countries between 2019 and 2023. The following research question was formulated – which European Union countries are leading, and which are at the bottom of the ranking in terms of the level of development of cashless payment? Methodology. The source of data on non-cash transactions was statistical data from the European Central Bank's ECB Data Portal. The method of linear ordering – standardized sums – was used to create a ranking of the European Union countries in terms of the level of development of cashless payment. Results of the research. An empirical study using the method of standardized sums made it possible to compare the level of development of cashless payment in the EU-27 countries and to identify the leaders and laggards in this respect. The results of the study proved that in the EU-27 countries, non-cash trading develops at a high and medium level. The leaders in this respect included Germany, France and Italy, while the worst ranked countries were Malta, Bulgaria, Latvia, Estonia and Cyprus. The reason for the underdevelopment of cashless payment in these countries can be attributed to an underdeveloped payment infrastructure, fewer institutions offering payment services, lower levels of investment in modern technology, and a payment culture that may be due to a tradition of attachment to cash and a lack of confidence in cashless forms of payment. In addition, the lack of appropriate regulation and government initiatives may influence their lower popularity.